Phosphate Uptake and Allocation – A Closer Look at Arabidopsis thaliana L. and Oryza sativa L. - Młodzińska, Ewa; Zboińska, Magdalena (Frontiers in Plant Science, 2016)
This year marks the 20th anniversary of the discovery and characterization of the two Arabidopsis PHT1 genes encoding the phosphate transporter in Arabidopsis thaliana. So far, multiple inorganic phosphate (Pi) transporters have been described, and the molecular basis of Pi acquisition by plants has been well characterized. These genes are involved in Pi acquisition, allocation and/or signal transduction. This review summarizes how Pi is taken up by the roots and further distributed within two plants: Arabidopsis thaliana and Oryza sativa L. by plasma membrane phosphate transporters PHT1 and PHO1 as well as by intracellular transporters: PHO1, PHT2, PHT3, PHT4, PHT5 (VPT1), SPX-MFS and phosphate translocators family. We also describe the role of the PHT1 transporters in mycorrhizal roots of rice as an adaptive strategy to cope with limited phosphate availability in soil.